Preparação e caracterização de triacetato de celulose a partir da polpa Kraft: aplicação na imobilização de lipase e catálise de reações de transesterificação - Silva, Francielle Batista da (2017)
The use of natural and /or semi-synthetic polymers as carriers for enzymes is a strategy for stabilizing enzymes, increasing the catalytic activity and removal of the enzyme from the reaction medium. In this work, cellulose triacetate (TAC) was produced by homogeneous acetylation reaction of Kraft pulp and a commercial phospholipase Lecitase Ultra® (LU) was immobilized in TAC by physical adsorption. TAC and LU immobilized in TAC (LU-CTA) were characterized by Infrared Spectroscopy (FTIR), High Angle X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Thermogravimetry (TGA). TAC production was confirmed by degree of substitution obtained by FTIR, equal to 2.7 and melting temperature of 306 oC. LU-TAC presented catalytic activity of 975.8 U/g, thermal stability, especially at temperatures between 35 and 40 oC, with inactivation of 24 and 19.3%, respectively, in 8 hours of experiment. LU-TAC also showed stability throughout a studied pH range. In the presence of n-hexane, in the first 6 h of incubation, LU-CTA showed increase in enzymatic activity. In the desorption studies, we observed a removal of 84.5% of lipase in the presence of a 0.02% Triton X-100 aqueous solution. The kinetic parameters, Km and Vmax, were obtained for LU (0.24 mmol/L and 11.07 μmol / min / mL, respectively) and LU-TAC (0.41 mmol/L and 7.09 μmol / min / mL, respectively). Results show changes in catalytic activity that may be associated with the interaction of the support to an enzyme. LU-TAC reuse tests indicated that the relative enzyme activity remained above 50% for two cycles. The performance of the LU-CTA system was evaluated in transesterification reactions of soybean oil with methanol for biodiesel production. Biodiesel production process was optimized, leading to an optimum working station: temperature of 34.2 °C, 21.9 % of LU-TAC and 7.7 % of water. A percentage of total esters obtained under these conditions was 48.4%, maintaining fixed molar ratio of oil / methanol 1: 4 and concentration of n-hexane equal to 0.5mL / g of oil. The results shown that the use of TAC stabilizes the enzyme and favors the use in biodiesel production.